A Family of Gods : The Worship of the Imperial Family in the Latin West - McIntyre, Gwynaeth (Book collections on Project MUSE., 2016)
Roman politics and religion were inherently linked as the Romansattempted to explain the world and their place within it. As Roman territory expanded and power became consolidated into the hands of oneman, people throughout the empire sought to define their relationship with the emperor by granting honors to him. This collection of practices has been labeled "emperor worship" or "ruler cult," but this tells only half the story: imperial family members also became an important partof this construction of power and almost half of the individuals deified in Rome were wives, sisters, children, and other family members of the emperor. "A Family of Gods" seeks to expand current "ruler cult" discussions by including other deified individuals, and by looking at how communities in the period 44 BCE to 337 CE sought to connect themselves with the imperial power structure through establishing priesthoods and cult practices. It focuses on the priests dedicated to the worship of the imperial family in order to contextualize their role in how imperial power was perceived in the provincial communities and the ways in which communities chose to employ religious practices.